Weapons of mass destruction : costs versus benefits - Bailey, Kathleen C.; Bailey, Kathleen C. (New Delhi : Manohar Publishers & Distributors, 1994)
Contributed articles.
Keywords: Weapons of mass destruction; Arms race -- Cost effectiveness